2015
DOI: 10.1186/s13072-015-0025-5
|View full text |Cite
|
Sign up to set email alerts
|

Gene repositioning within the cell nucleus is not random and is determined by its genomic neighborhood

Abstract: BackgroundHeterochromatin has been reported to be a major silencing compartment during development and differentiation. Prominent heterochromatin compartments are located at the nuclear periphery and inside the nucleus (e.g., pericentric heterochromatin). Whether the position of a gene in relation to some or all heterochromatin compartments matters remains a matter of debate, which we have addressed in this study. Answering this question demanded solving the technical challenges of 3D measurements and the larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 61 publications
2
13
0
1
Order By: Relevance
“…Although individual alleles are stably positioned in space and time, different chromosomes have unique positions. These findings are consistent with results of fixed cells and the chromosome territory models 5 , 7 , 43 . We also found that allele positions are preserved and similar in live cells, irrespective of the genetic backgrounds (129S1/CAST) in 3D- and 4D-imaging.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although individual alleles are stably positioned in space and time, different chromosomes have unique positions. These findings are consistent with results of fixed cells and the chromosome territory models 5 , 7 , 43 . We also found that allele positions are preserved and similar in live cells, irrespective of the genetic backgrounds (129S1/CAST) in 3D- and 4D-imaging.…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were obtained by studying chromosomal territories, where each territory showed a unique pattern with minor differences between homologous chromosomes in fixed cells 29 . A broader analysis is required to dissect the characteristic chromosomal features of size, gene density 9 , transcriptional activity 44 , local chromatin states and protein recruitment 5 , 43 , and whether or not they directly influence allele positioning proportional to the spatial order of whole chromosomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, artificial anchoring of distinct genes to the nuclear lamina leads to their reversible repression [9294], but this re-positioning occurs only after a passage through mitosis [93]. Tethering to the periphery is sufficient to suppress the expression of some but not all genes [92,95,96], implying the existence of different sensitivity classes of genes, as was found with the RT studies discussed above. Although RT was not measured in these studies, since the periphery is a late replicating compartment such analogies are reasonable to expect.…”
Section: Twisting the Lion’s Tailmentioning
confidence: 99%
“…Normally, the positioning of genes during interphase is constrained, and only mitosis-mediated changes or major gene expression changes can lead to gene repositioning within the nucleus (Chubb et al, 2002;Kumaran & Spector, 2008;Ferrai et al, 2010). Gene positions are dependent on the chromatin neighborhood and are not randomly located within the nucleus (Jost et al, 2015). Generally, transcriptionally active loci tend to be in the nuclear center, whereas silenced genes are located closer to the nuclear periphery, which is associated with heterochromatin (Peric-Hupkes et al, 2010).…”
Section: Introductionmentioning
confidence: 99%